2005
DOI: 10.1007/11564751_8
|View full text |Cite
|
Sign up to set email alerts
|

Inter-distance Constraint: An Extension of the All-Different Constraint for Scheduling Equal Length Jobs

Abstract: Abstract. We study a global constraint, the "inter-distance constraint" that ensures that the distance between any pair of variables is at least equal to a given value. When this value is 1, the inter-distance constraint reduces to the all-different constraint. We introduce an algorithm to propagate this constraint and we show that, when domains of the variables are intervals, our algorithm achieves arc-B-consistency. It provides tighter bounds than generic scheduling constraint propagation algorithms (like ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, initial experiments have shown that this almost never happens while the use of additional variables is costly. Recently, Artiouchine and Baptiste (2005) and Quimper et al (2006) studied the "interdistance constraint" that ensures that the distance between any pair of variables is at least equal to a given value. They describe a polynomial time algorithms to achieve arc-B-consistency (arc-consistency restricted to bounds of domains).…”
Section: Schedulingmentioning
confidence: 99%
“…However, initial experiments have shown that this almost never happens while the use of additional variables is costly. Recently, Artiouchine and Baptiste (2005) and Quimper et al (2006) studied the "interdistance constraint" that ensures that the distance between any pair of variables is at least equal to a given value. They describe a polynomial time algorithms to achieve arc-B-consistency (arc-consistency restricted to bounds of domains).…”
Section: Schedulingmentioning
confidence: 99%